2021
DOI: 10.48550/arxiv.2103.04001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Black Hole Leftovers: The Remnant Population from Binary Black Hole Mergers

Zoheyr Doctor,
Ben Farr,
Daniel E. Holz

Abstract: The inspiral and merger of two black holes produces a remnant black hole with mass and spin determined by the properties of its parent black holes. Using the inferred population properties of component black holes from the first two and a half observing runs of Advanced LIGO and Virgo, we calculate the population properties of the leftover remnant black holes. By integrating their rate of formation over the age of the universe, we estimate the number density of remnant black holes today. Using simple prescript… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Our estimates can be compared with those in Doctor et al ( 2021 4% and 40% for clusters with escape speeds of 50 km/s and 250 km/s. This broadly agrees with our numbers, though the retention probability in Doctor et al (2021) is quantified using the hyperparameters that describe the GWTC-2 population.…”
Section: Characterizing Clusters Via Their Retention Of Bh Merger Rem...supporting
confidence: 87%
See 1 more Smart Citation
“…Our estimates can be compared with those in Doctor et al ( 2021 4% and 40% for clusters with escape speeds of 50 km/s and 250 km/s. This broadly agrees with our numbers, though the retention probability in Doctor et al (2021) is quantified using the hyperparameters that describe the GWTC-2 population.…”
Section: Characterizing Clusters Via Their Retention Of Bh Merger Rem...supporting
confidence: 87%
“…Note that binaries containing higher-spinning BHs typically experience larger kicks as compared to binaries with low-spin BHs, and can thus be more easily ejected from clusters. Doctor et al (2021) mapped the properties of GWTC-2 BH remnants to the statistical properties of remnant BHs in our universe. They obtained the distribution of kick velocities of GWTC-2 events using NR surrogate waveform models (Varma et al 2019b,a) and found that globular clusters and nuclear clusters can retain ∼ 4% and 45% of the remnants, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…83 For those few cases, we implement expressions for final mass, 85 spin, 86 and recoil 87 which explicitly include the test-particle limit. See Doctor et al 88 for a study dedicated to the distribution of post-merger remnants extrapolated from the current LIGO/Virgo detections.…”
Section: A Simple Realizationmentioning
confidence: 99%
“…A slightly different hierarchical merger spin distribution is reported by [68] based on the priors from LIGO/VIRGO data for mergers limited to the Milky Way. This distribution also peaks at a * 0.7.…”
Section: Pbh Spin Distribution From Inspiralsmentioning
confidence: 73%